Pembuatan dan Uji Kinerja Mesin Pemipil Jagung Ban - Agrisda Hasansyah Putra; Ramdan Darmawan; Supriyono Supriyono; Rizza Wijaya (JOFE : Journal of Food Engineering, 2022)
A tire type corn sheller design is intended to assist in shelling corn for seed. The use of car tires instead of cylinders is intended to minimize damage to corn kernels. This sheller machine consists of main components: frame, sheller tire, concave, corn cob extraction, corn kernel extraction, and bearings. The engine is driven by a 6.5 HP petrol motor which is connected via belts and pulleys which transmit torque from the motor to the tire sheller shaft. The prototype of this machine has been tested for its performance and obtained shelling efficiency of 83.39% with a capacity of 87.92 kg/hour of shelled corn. Machines are easy to make with easily available materials that are relatively cheap and affordable, portable so that they are suitable for farmers in rural areas.